Postcardiotomy Venoarterial Extracorporeal Membrane Oxygenation in Patients Aged 70 Years or Older - Fausto Biancari; Diyar Saeed; Antonio Fiore; Magnus Dalén; Vito G.Ruggieri; Kristján Jónsson; Giuseppe Gatti; Svante Zipfel; Angelo M.Dell’Aquila; Sidney Chocron; Karl Bounader; Gilles Amr; et al. (ELSEVIER SCIENCE INC, 2022)
Background. There is uncertainty whether venoarterial extracorporeal membrane oxygenation (VA-ECMO) should be used in older patients with cardiopulmonary failure after cardiac surgery.Methods. This was a retrospective multicenter study of 781 patients who required postcardiotomy VA-ECMO for cardiopulmonary failure after adult cardiac surgery from 2010 to 2018 at 19 cardiac surgery centers. A parallel systematic review with meta-analysis of the literature was performed.Results. The hospital mortality in the overall Post-cardiotomy Venoarterial Extracorporeal Membrane Oxygenation (PC-ECMO) series was 64.4%. A total of 255 patients were 70 years old or older (32.7%), and their hospital mortality was significantly higher than in younger patients (76.1% vs 58.7%; adjusted odds ratio, 2.199; 95% confidence interval [CI], 1.536 to 3.149). Arterial lactate level greater than 6 mmol/L before starting VA-ECMO was the only predictor of hospital mortality among patients 70 years old or older in univariate analysis (82.6% vs 70.4%; P = .029). Meta-analysis of current and previous studies showed that early mortality after postcardiotomy VA-ECMO was significantly higher in patients aged 70 years or older compared with younger patients (odds ratio, 2.09; 95% CI, 1.59 to 2.75; 5 studies including 1547 patients; I-2, 5.9%). The pooled early mortality rate among patients aged 70 years or older was 78.8% (95% CI, 74.1 to 83.5; 6 studies including 617 patients; I-2, 41.8%). Two studies reported 1-year mortality (including hospital mortality) of 79.9% and 75.6%, respectively, in patients 70 years old or older.Conclusions. Advanced age should not be considered a contraindication for postcardiotomy VA-ECMO. However, in view of the high risk of early mortality, meaningful scrutiny is needed before using VA-ECMO after cardiac surgery in older patients. (C) 2019 by The Society of Thoracic Surgeons